PERKEMBANGAN OOSIT IKAN PATIN SIAM, Pangasianodon hypophthalmus Sauvage, 1878 (PANGASIIDAE; SILURIFORMES) - Evi Tahapari; Bambang Iswanto (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Pangasianodon hypophthalmus is an introduced species of fish culture and fisheries resources in Indonesia. Reproductive biology aspects, e.g. maturity, plays an important role on the fisheries management. There was no detail information of oocytes development of P. hypophthalmus. The aim of this study is to find out the detail of its oocytes development through the observation of whole oocytes and ovarian histological slides microscopically. The results showed that the rhythm of oocyte development of P. hypophthalmus was grouped synchronism, assigned by the presence of two oocyte groups in the mature females, i.e. the large and maturing oocytes which would be spawned soon, and the small ones as the stock and still unyolked for the next spawning. The oocyte development could be devided into five stages, i.e. stage 1 (chromatin nucleolar and perinucleolar) with oocytes diameter less than 300 urn, stage 2 (yolk vesicles and cortical alveolar) with oocytes diameter of 230-660 urn, stage 3 (yolk granules) with oocytes diameter of 430-1,100 urn, stage 4 (migratory nucleus and hydrated) with oocytes diameter of 950-1,260 urn, and stage S (atretic) with oocytes diameter less than 800 m